Anasazi America : Seventeen Centuries on the Road from Center Place - Stuart, David E. (Book collections on Project MUSE., 2000)
"At the height of their power in the late eleventh century, the Chaco Anasazi dominated a territory in the American Southwest larger than any European principality of the time. A vast alliance of hamlets and towns integrated the region through economic and religious ties, and the whole system was interconnected with hundreds of miles of roads. It took these Anasazi farmers more than seven centuries to create classic Chacoan civilization, which lasted some 200 years - only to collapse spectacularly in a mere 40." "Why did such a great society collapse? Who survived? Why? In this lively book anthropologist/archaeologist David Stuart presents answers to these questions that offer useful lessons to modern societies. His account of the rise and fall of the Chaco Anasazi brings to life the people who are know to us today as the architects of Chaco Canyon, now a spectacular national park in northwestern New Mexico."--Jacket